VISUALISASI KARAKTER GELOMBANG LISSAJOUS PADA OSILOSKOP MENGGUNAKAN SPREADSHEET MICROSOFT EXCEL PADA PEMBELAJARAN FISIKA - Mouromadhoni, Kasyfi Rifqi; Kuswanto, Heru (EDUSAINS, 2019)
VISUALIZATION OF LISSAJOUS WAVE CHARACTER IN OSCILLOSCOPE USING SPREADSHEET MICROSOFT EXCEL IN PHYSICS LEARNINGÂ AbstractThis study examines the visualization of the creation and operation of lissajous waves on the oscilloscope screen using a spreadsheet on Microsoft Excel 2013. The purpose of this research is to produce a visualization and how to operate lissajous waves using Microsoft Excel. The subject of this research is a spreadsheet program on Microsoft Excel software. Research location in the Yogyakarta State University Postgraduate Program building. The results of the study are expected to produce a visualization of how and how to operate a lissajous wave using Microsoft Excel. The data used uses fixed amplitude, frequency ratio 1:1 (a=1, b=1) with different phases at special angles ie 0o, 30o, 60o dan 90o. As well as other data with different frequency comparisons but using fixed amlitudes and phase differences of 90o. Comparison of frequency, amplitude and phase difference has the main role in forming lissajous wave patterns. It can be concluded that the speadsheets program on Microsoft Excel 2013 can be used to create simulations and describe lissajous wave patterns on oscilloscope screens in physics learning. Through simulation of lissajous wave patterns using spreadsheets on Microsoft Excel can make it easier for students and teachers to understand the lissajous curve on the oscilloscope screen. AbstrakPenelitian ini mengkaji tentang visualisasi pembuatan dan pengoperasian gelombang lissajous pada layar osiloskop menggunakan spreadsheet pada microsoft excel 2013. Tujuan penelitian menghasilkan visualisasi dan cara pegoperasian gelombang lissajous menggunakan microsoft excel. Subjek penelitian ini adalah program spreadsheet pada software microsoft exel. Lokasi penelitian di gedung Program Pascasarjana Universitas Negeri Yogyakarta. Hasil penelitian diharapkan dapat menghasilkan visualisasi pembuatan dan cara pegoperasian gelombang lissajous menggunakan microsoft excel. Data yang digunakan menggunakan amplitudo tetap, perbandingan frekuensi 1:1 (a=1, b=1) dengan beda fase pada sudut istimewa yaitu 0o, 30o, 60o dan 90o. Serta data lain dengan perbandingan frekuensi yang berbeda namun menggunakan amlitudo tetap dan beda fase sebesar 90o. Perbandingan frekuensi, amplitudo dan beda fase memiliki peran utama dalam pembentukkan pola gelombang lissajous. Dapat disimpulkan bahwa program speadsheets pada miscrosoft excel 2013 dapat digunakan untuk membuat simulasi dan menggambarkan pola gelombang lissajous pada layar osiloskop dalam pembelajaran fisika. Melalui simulasi pola gelombang lissajous menggunakan spreadsheets pada microsoft excel dapat memudahkan siswa maupun guru dalam memahami kurva lissajous pada layar osiloskop.Â